Effect of 1-metylciclopropene application on some physicochemical and organoleptic properties of sweet passion fruit (2011)
Shelf life extension of the sweet passion fruit is helpful for its marketing, since it is positioned in the international market as a gourmet fruit. In this work the effect of applying an antagonistic agent to the ethylene action was evaluated, 1- methylcyclopropene (1-MCP) was used to prolonged shelf life of sweet passion fruit, stored of 27 ± 2 °C and 76 ± 2% RH. Physical properties as weight loss, firmness loss and color changes were evaluated, together with chemical properties such as pH, acidity and soluble solids and sensory analysis. Three concentrations of 1-MCP: 200, 400 and 600 mg/l with three exposure times: 15, 30 and 60 seconds were applied. The results suggest that application of 600 mg/l of 1-MCP for 60 seconds of exposure preserves the fruit during 15 days at 27 ± 2°C and 76 ± 2% of HR.